Model of success: Extension services helping Ugandan youth find a career in agriculture - Lamm, Kevan W.; Mulvaney, Chandler; Lamm, Alexa J.; Davis, Kristin E.; Masambuka-Kanchewa, Fallys; Nahdy, Silim (Association for International Agricultural and Extension Education, 2021)
As the world continues to experience a population boom amidst growing food insecurity concerns, the need for well-trained and competent youth in agriculture-related industries is on the rise in Sub-Saharan African countries, specifically Uganda. With 78 percent of Uganda’s population below the age of thirty, the number of unemployed and unskilled workers presents a challenge to a country that relies heavily on jobs within the agricultural sector to thrive. Due to the increased number of unskilled youths, extension-based services such as the National Agriculture Advisory Services (NAADS) and the Uganda Forum for Agricultural Advisory Services (UFAAS) are needed to connect with youth organizations to provide training and direction for those seeking careers in agriculture. This study sought to better understand the phenomena of competency development through various communication channels used to facilitate leadership development and agricultural literacy within a youth organization known as Nokia Farming Agricultural Innovation Platform (NOFAIP). A single instrumental case study was conducted to assess the career preparedness of youth within the NOFAIP group and opportunities that exist for employment within agriculture-related industries. Results found that upon receiving training from UFAAS, the NOFAIP group had increased their credibility amongst Ugandan farming communities and supported the growth of agricultural competencies, such as soil testing, using backpack sprayers to spread fertilizers, and managing citrus groves. Through hands-on experiences and engagement with appropriate training, the NOFAIP group established communication channels that were critical to experience personal growth and the invigoration of an entrepreneurial spirit within agriculture.